KAJIAN KANDUNGAN KIMIA DAN PENILAIAN SENSORI SOSIS AYAM DENGAN PENAMBAHAN JAMUR MERANG (Volvariella volvaceae) - Heri ' Idrus; Evy ' Rossi; Rahmayuni ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose oh this research was to determine the effect of straw mushroom on chicken meat sausage. This study was conducted experimentally by using a completely randomized design (CRD) with four treatments and four replications. The treatments in this research were ratio chicken meat (A) with straw mashroom (J), that were A1J1 (A:J = 100:0), A2J2 (A:J = 95:5), A3J3 (A:J = 90:10), A4J4 (A:J =85:15). The data obtained were analyzed statistically using ANOVA and DNMRT at a level of 5%. The results of this study showed that the ratio of chicken meet (A) to straw mashroom (J) gave significant effect on water, ash, protein, fiber, sensory of assessment of the color, aroma, flavor, texture and overall assessment sausage. The best treatment in this research was A3J3 with a water, protein, ash, and fiber content, respectively 41.53%, 14.48%, 1.98%, and 0.08% . The descriptive sensory assessment for color was gray (3.06), rather flavorful sausage (1.9), tasteless sausage (2.70), slightly chewy texture (1.73) as well as an overall assessment that 2.36 (like). Based on the results of chemical analysis and sensory analysis of sausage, it was concluded that the best treatment was A3J3. Keyword : Sausage, straw mushroom and sausage mushrooms